2022-RA-994-ESGO Evaluation of one step nucleic acid amplification (OSNA) method for rapid detection of lymph node metastases in women with endometrial cancer. (20th October 2022) - Fera, Eleonora La; Petrecca, Alessandro; Monterossi, Giorgia; Restaino, Stefano; Scambia, Giovanni; Fanfani, Francesco
Abstract : Introduction/Background: The objective of this study is to establish the clinical performance of the One Step Nucleic Acid Amplification (OSNA) method for the detection of sentinel lymph node (SNL) metastases in women with early-stage endometrial cancer (EC) compared to standard Ultrastaging (US). Methodology: This is a prospective, multicentric, observational study, women with early-stage EC underwent surgical staging with SNL identification. SNLs were serially sectioned at 2 mm slices thickness perpendicular to the longest axis of the node, the odd slices were submitted to ultra-staging, according to our institutional ultrastaging protocol, even slices were submitted to the OSNA analysis. Results: This is the largest study, until now, with three-hundred-and-sixteen patients enrolled with 668 SNLs analyzed with the two methods OSNA and US. OSNA assay detected 22 (3, 3%) positive SNLs of which 17 (2, 5%) micrometastases, and 5 (0, 7%) macrometastases, whereas pathological ultrastaging detected 24 (3, 6%) positive SNLs of which 15 (2, 2%) micrometastases and 9 (1, 3%) of macrometastases. In addition, OSNA detected 649 negative nodes (including 8 ITC), while Ultrastaging 644 negative nodes (with 26 ITC.) Using Ultrastaging as a reference method the specificity of 98, 4%, the diagnostic accuracy of 96, 7%, and the negative predictive value of 98, 1% were attended. Discordant results were found in 22 SNLs (3, 2%) corresponding to 20 patients (6, 3%). We found 10 false-positive SNLs, all micrometastases, and 12 false-negative lymph nodes of which 9 micrometastases and 3 macrometastases. Conclusion: Although only portions of a whole lymph node have been examined with OSNA analysis, it has proved to be highly specific with high diagnostic accuracy, a high negative predictive value, and moderate concordance with the standard US. Therefore, we believe that OSNA is a valid method for analyzing lymph node metastases in patients with apparent early-stage EC, which allows us to analyze the entire lymph node with a standardized method.